A CRITICAL EXAMINATION OF THE PHILOSOPHY OF SCIENCE FROM WESTERN AND ISLAMIC PERSPECTIVES - Millatina, Nurma; As-Syafi’i, Rizka` Putri (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
This research discusses the philosophy of science from a Western and Islamic perspective. Philosophy of science is a branch of philosophy that discusses the fundamental characteristics of science systematically. In the study of philosophy of science, there are two most prominent camps, namely Western philosophy of science and Islamic philosophy of science. Both have their own backgrounds, perspectives and characteristics. From here, this research intends to re-examine Western philosophy of science and Islamic philosophy of science critically and comprehensively, to produce a complete understanding by looking at the results of analyzing the similarities and differences between Western and Islamic philosophy of science. This study uses a qualitative research method with a literature study approach to collect theories from various sources that are related and can be used to solve research problems. Through literature study, data collection in this study is carried out by examining various books, literature, reports and notes relevant to the philosophy of science in Western and Islamic views. From this research, it is found that in both Western and Islamic philosophy of science, there is a deep concern for the search for truth, the use of reason, scientific research methodology, the concept of causality, and the relationship between religion and science. Western philosophy of science and Islamic philosophy of science have significant differences in various aspects, including the foundations of epistemology, theology, approaches to science, and cultural influences.